Tripled fixed points theorems for ø-contractive mixed monotone operators on partially ordered metric spaces - Charoensawan P. (2014)
In this paper, we prove tripled fixed point theorem for nonlinear ø-contractive mixed monotone on partially ordered complete metric spaces. We also prove the uniqueness of tripled fixed point of such mappings under some comparable conditions.